Taxonomic reinstatement of Metzgeria mitrata (Marchantiophyta: Metzgeriaceae) and its red list assessment - Singh, Devendra; Ali, Sk Nasim (Phytotaxa, 2025)
The taxonomic status of Metzgeria mitrata is evaluated and determined to be a distinct species from M. furcata. The threatened status of the species has been assessed for the first time as ‘Critically Endangered (CR)’ by applying the Criteria B of IUCN Red List Categories and Criteria Version 16.